Taklik Talak Perspektif Ulama Mazhab dan Pengaruhnya dalam Berumah Tangga - Sofyan Yusuf; Moh Toriqul Chaer (Institut Ilmu Keislaman Annuqayah, 2017)
Taklik talak controversy which contained in articles 45 and 46 in the compilation of Islamic law (KHI) does not only occur among mazhab scholars, but also community. This is because of taklik talak influential in the household life. This study used a qualitative descriptive method. The data was collected through observation, interview, documentation and was analyzed qualitatively. The study finding as follow: First, the majority of Islamic Scholars assumed that the fall of divorce when a swear in. Second, Ibn Hazm and Ibn Qayyim al-Jauziyah argued that the taklik containing oath (qasam) does not causing divorce. Third, an understanding of the related society, including divorce, taklik: 1) reading of sigat taklik is a form of guarantee of the husband; 2) contents of sighat taklik is the covenant of marriage between a husband and wife, and signed, not just spoken only; 3) agreement is not obligatory agreement taklik talak which should be held on any marriage, but once divorce already enforced by taklik, then it cannot be revoked.